Immunoreactive Cells After Cerebral Ischemia - Wang, Yijie; Zhang, John H.; Sheng, Jifang; Shao, Anwen (Frontiers in Immunology, 2019)
The immune system is rapidly activated after ischemic stroke. As immune cells migrate and infiltrate across the blood-brain barrier into ischemic region, a serial cellular and molecular biological reactions occur, involving migrated immune cells, resident glial cells, vascular endothelium, regulating the evolution of infarction, and thus influence the outcome of ischemic stroke. Most of the immune cells are found to have dual effects on cerebral ischemia, and some crucial cells may become central targets in ischemic stroke treatment and rehabilitation.